Juvenile Hormone Is an Important Factor in Regulating Aspongopus chinensis Dallas Diapause - Zhou, Wen-Zhen; Wu, You-Fang; Yin, Zhi-Yong; Guo, Jian-Jun; Li, Hai-Yin (Frontiers in Physiology, 2022)
The absence of juvenile hormone induces reproductive diapause in many insects. In insects, the process whereby juvenile hormone regulates reproductive diapause has been previously investigated. However, how juvenile hormone Ⅲ physiologically could contribute to development of reproduction and terminate diapause is remains largely unclear. Aspongopus chinensis Dallas, 1851 is a Chinese important traditional edible and medicinal insect. Its diapause for up to 7 months and the insect yield is very low. In this paper, we investigated the relationship between JH and diapause. Measured reproductive system development and fat content after injected JHⅢ. And then reproductive system development, fat content, juvenile hormone content and mating time after RNAi mediated JHEH and JHAMT were determined. Our data indicate that the JHⅢ in diapause was lower significantly than that in diapause termination of A. chinensis. After treatment with 50 ng/μL exogenous juvenile hormone, reproductive system of diapause A. chinensis resumed development. The mating behavior reaches 91.6% after 30 days. Meanwhile, there is pronounced fat body consumption. JH and fat biosynthesis gene were up-regulated, JH degradation gene were down-regulated. dsJHEH can interfere in the expression of JHEH, and significantly increase JH content in the body. JH content will reach to a tiptop of 408.31±7.56 ng/g in a short time. The reproductive system of A. chinensis will develop and perfect in advance. The mating behavior appears on the 52.00±0.58 day, which is significantly earlier than the control group by about 6-9 days. During the progress, the lipid consumption was significant. After interfering in JHAMT, the production of JH, the development of the reproductive system and the consumption of lipids are significantly inhibited. And the mating behavior appears on the 77.67±1.20 day, compared with the control group, it is significantly delayed by about 17-19 days. Therefore, we demonstrate that higher or lower concentrations of JH can maintain or terminate diapause state. And JH can terminate diapause mainly by promoting the development of the reproductive system and accelerating fat consumption.